Wide-temperature-range lithium battery electrolyte and preparation method thereof

CN122025826BActive Publication Date: 2026-10-16ANHUI XINGLI NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610304710.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-13
Publication Date
2026-10-16
Estimated Expiration
2046-03-13

AI Technical Summary

Technical Problem

现有改进手段通常通过引入低凝点共溶剂、提高盐浓度或配置多功能添加剂来分别改善低温传输或高温稳定,但这类调整往往伴随另一端温区的副作用:低温友好的溶剂/添加剂可能提高高温反应活性与产气倾向,而高温稳定导向的体系又可能提高黏度与界面阻抗,使低温快充更加受限;同时制造与使用中不可避免的微量水/酸与材料差异会放大上述矛盾

Benefits of technology

电解液由组分A的低凝点碳酸酯与羧酸酯形成低黏溶剂基体,并与组分B的腈类溶剂和磷酸酯溶剂配合,兼顾低温浸润与高电压氧化稳定。组分C采用六氟磷酸锂、双氟磺酰亚胺锂、二氟草酸硼酸锂及二氟磷酸锂的复合锂盐体系,在维持集流体适配的同时提升低温离子传输并提供无机成膜来源,组分D的乙烯亚硫酸酯促使负极快速生成薄而导离子的界面膜。组分E由多官能环氧单元、氢氟酸触发的潜伏多元醇与硼酸酯调制单元组成,当高温副反应产生氢氟酸和五氟化磷时,潜伏多元醇优先清除酸并释放羟基,继而与多官能环氧在电极界面限域环开交联,硼酸酯引入可重排键以实现界面自修复与传导。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122025826B_ABST
    Figure CN122025826B_ABST
Patent Text Reader

Abstract

The application discloses a wide-temperature-range lithium battery electrolyte and a preparation method thereof, relates to the technical field of lithium battery electrolytes, and is oriented to low-temperature fast charging and high-temperature full-charge storage. The electrolyte contains components A to E: component A is a linear carbonate and a low-freezing-point carboxylate; component B is a nitrile solvent and a phosphate solvent; component C is a multi-lithium salt system; component D is ethylene sulfite; and component E is an acid-triggered cross-linking self-repairing interface reinforcing agent, which comprises a multifunctional epoxy unit, a latent polyol capable of triggering the release of hydroxyl groups by an acidic species, and a borate dynamic modulation unit. In the preparation, moisture is controlled under an inert atmosphere, a solvent mother liquor is first prepared, and salt dissolution is carried out in steps, then component D and component E are sequentially added and filtered and sealed. The electrolyte maintains low viscosity and ion transmission at low temperature, reduces the risk of lithium precipitation, inhibits gas production and interface deterioration at a high-temperature state of charge, avoids bulk phase thickening, and improves cycle and storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery electrolyte technology, specifically to a wide-temperature-range lithium battery electrolyte and its preparation method. Background Technology

[0002] With the large-scale application of electric vehicles and electrochemical energy storage systems in cold regions, winter outdoor charging, and summer high-temperature parking / storage conditions, power and energy storage batteries are required to maintain usable power, efficiency, and lifespan over a wide range of ambient temperatures, especially achieving high-rate charging at low temperatures and withstanding high-charge storage at high temperatures without excessive gas expansion. Currently, most industrialized lithium-ion batteries use non-aqueous liquid electrolyte systems, typically employing lithium hexafluorophosphate as the lithium salt, carbonate as the solvent, and a small amount of additives to form an interfacial film supporting materials such as graphite anodes and high-nickel cathodes. As high-nickel cathodes increase operating voltage, silicon-based components increase anode capacity, and "low-volume" designs place higher demands on wetting and transport, the bulk transport and interfacial stability of the electrolyte over a wide temperature range become limiting factors.

[0003] In low-temperature environments (e.g., −20°C and below), solvent viscosity increases, and salt dissociation and diffusion slow down, leading to decreased ionic conductivity and worsened desolvation / charge transfer kinetics, which in turn increases polarization. During fast charging, the local potential of the negative electrode may exceed the lithium plating threshold, resulting in lithium metal deposition and uneven growth, inducing irreversible lithium loss, increased impedance, and potential safety risks. Conversely, at high temperatures (e.g., 55–60°C) and under high charge conditions, the electrolyte is more prone to oxidative decomposition and salt-related side reactions. Trace amounts of moisture can promote the formation of acidic species and accelerate the dissolution / regeneration of the positive and negative electrode interfacial film, transition metal dissolution, and accumulation of gaseous byproducts, manifesting as soft pack swelling, increased internal pressure, accelerated capacity decay, and uniform degradation. Existing improvement methods typically involve introducing low-pour-point co-solvents, increasing salt concentrations, or configuring multifunctional additives to improve low-temperature transport or high-temperature stability, respectively. However, such adjustments often come with side effects at the other end of the temperature range: low-temperature-friendly solvents / additives may increase high-temperature reactivity and gas production tendency, while high-temperature stability-oriented systems may increase viscosity and interfacial resistance, making low-temperature fast charging more limited; at the same time, the unavoidable trace amounts of water / acids and material differences during manufacturing and use will amplify the above contradictions.

[0004] Therefore, the core problem that existing technologies urgently need to solve is: How can the same electrolyte simultaneously meet the requirements of lithium plating suppression and low impedance under low temperature and high rate charging conditions, as well as the requirements of gas generation control and interface stability under high temperature and high charge storage or cycling conditions, while taking into account the wetting transport and manufacturing repeatability under small liquid volume conditions in practical applications of high nickel cathodes and graphite / silicon-based anodes? Summary of the Invention

[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a wide-temperature-range lithium battery electrolyte and its preparation method, comprising: component A, which is a linear carbonate and a low-pour-point carboxylic acid ester; component B, which is a nitrile solvent and a phosphate ester solvent; component C, which is a multi-lithium salt system; component D, which is ethylene sulfite; and component E, which is an acid-triggered crosslinking self-healing interface enhancer containing multifunctional epoxy units, a latent polyol that can be triggered by acidic species to release hydroxyl groups, and a borate ester dynamic modulation unit. During preparation, moisture is controlled under an inert atmosphere. A solvent stock solution is first prepared and the salt is dissolved stepwise, then components D and E are added sequentially, followed by filtration and sealing. This electrolyte maintains low viscosity and ion transport at low temperatures, reducing the risk of lithium plating; and suppresses gas generation and interface degradation and avoids bulk thickening under high-temperature charged conditions, solving the technical problems described in the prior art.

[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: A wide-temperature-range lithium battery electrolyte comprises a solvent system, a lithium salt, ethylene sulfite, and component E; the solvent system comprises linear carbonates, low-pour-point carboxylic esters, nitrile solvents, and phosphate ester solvents; the lithium salt is lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalate borate, and lithium difluorophosphate, with a total lithium salt concentration of 0.9 to 1.3 mol / L; component E comprises 0.2 to 2.5% by mass of a multifunctional epoxy unit, 0.05 to 1.2% by mass of 1,4-butanediol bis(tert-butyldimethylsilyl) ether, and 0.05 to 0.6% by mass of tributyl borate, wherein the multifunctional epoxy unit contains polyethylene glycol diglycidyl ether and 1,3-bis(3-glycidyl etherpropyl)tetramethyldisiloxane, and the ratio of the epoxy equivalent of the multifunctional epoxy unit to the hydroxyl equivalent released by 1,4-butanediol bis(tert-butyldimethylsilyl) ether is 0.7 to 2.5.

[0007] Furthermore, based on the total mass of the solvent, the linear carbonate is 35% by mass of ethyl methyl carbonate and 20% by mass of diethyl carbonate, the low-pour-point carboxylic acid ester is 10% by mass of ethyl propionate, the nitrile solvent is 25% by mass of 3-methoxypropionitrile, and the phosphate ester solvent is 10% by mass of triethyl phosphate.

[0008] Furthermore, the lithium hexafluorophosphate is 0.65 mol / L, the lithium bis(fluorosulfonyl)imide is 0.25 mol / L, the lithium difluorooxalate borate is 0.08 mol / L, and the lithium difluorophosphate is 0.03 mol / L.

[0009] Furthermore, the ethylene sulfite content is 0.6 to 1.5% by mass.

[0010] Furthermore, the amount of polyethylene glycol diglycidyl ether added is 0.5 to 1.0% by mass, and its epoxy equivalent is 250 to 320 g per dose.

[0011] Furthermore, the amount of 1,3-bis(3-glycidyl ether propyl)tetramethyldisiloxane added is 0.1 to 0.6% by mass, and its molecule contains two epoxy groups.

[0012] Furthermore, the amount of 1,4-butanediol bis(tert-butyldimethylsilyl) ether added is 0.15 to 0.40% by mass, and its molecule contains at least two silyl ether bonds.

[0013] Furthermore, the amount of tributyl borate is 0.10 to 0.25% by mass, and the ratio of the number of boron centers in the tributyl borate to the hydroxyl equivalent released by 1,4-butanediol bis(tert-butyldimethylsilyl) ether is 0.05 to 0.4.

[0014] A method for preparing a wide-temperature-range lithium battery electrolyte includes the following steps: Under an inert atmosphere, ensure the water content of the solvent, lithium salt, and additives does not exceed 20 mg / kg; mix the solvent system and stir; under an inert atmosphere, first mix the solvent system and cool to 0–20°C; add lithium hexafluorophosphate in batches with stirring (using a jacket / ice-water bath for temperature control if necessary); at 20–30°C, first add lithium difluorooxalate borate and lithium difluorophosphate, then add lithium bis(fluorosulfonyl)imide, and finally stir until clear; add ethylene sulfite, multifunctional epoxy unit, and 1,4-butanediol bis(tert-butyldimethylsilyl) ether in sequence, then pre-dilute tributyl borate with the solvent system and add dropwise; filter and seal for storage.

[0015] Furthermore, after each substance is added, continue stirring for at least 20 minutes; filter using a 0.2-micron PTFE filter membrane; after filtration, pack into an aluminum bottle or fluorinated bottle, seal with argon, and store in the dark at 0 to 10 degrees Celsius.

[0016] (III) Beneficial Effects This invention provides a wide-temperature-range lithium battery electrolyte and its preparation method, which has the following beneficial effects: The electrolyte consists of a low-viscosity solvent matrix formed by low-pour-point carbonates and carboxylic esters in component A, combined with nitrile and phosphate solvents in component B, ensuring both low-temperature wetting and high-voltage oxidation stability. Component C employs a composite lithium salt system of lithium hexafluorophosphate, lithium difluorosulfonylimide, lithium difluorooxalate borate, and lithium difluorophosphate, which improves low-temperature ion transport and provides an inorganic film source while maintaining current collector compatibility. The ethylene sulfite in component D promotes the rapid formation of a thin, ion-conducting interfacial film at the negative electrode. Component E comprises multifunctional epoxy units, hydrofluoric acid-triggered latent polyols, and borate ester modulation units. When high-temperature side reactions produce hydrofluoric acid and phosphorus pentafluoride, the latent polyol preferentially removes the acid and releases hydroxyl groups, which then crosslink with the multifunctional epoxy at the electrode interface in a confined ring-opening manner. The borate ester introduces rearrangeable bonds to achieve interfacial self-repair and conduction.

[0017] By first dissolving the composite lithium salt and component D, then adding component E and filtering for degassing, the pre-reaction induced by localized high concentrations can be avoided, resulting in a stable and reproducible solvation structure and interfacial reaction pathway, thus improving impedance consistency under thin electrode conditions with low liquid volume. At low temperatures, this system reduces desolvation resistance and charge transfer resistance, enhancing charge acceptance. Therefore, without causing bulk thickening, it suppresses gas generation and swelling, slows transition metal dissolution, and reduces the induction of lithium plating during low-temperature fast charging, creating a synergistic effect beyond simple addition. Attached Figure Description

[0018] Figure 1 This is a schematic diagram illustrating the overall framework and component division of the wide-temperature-range electrolyte formulation of this invention; Figure 2 This is a schematic diagram of the acid-triggered crosslinking self-healing bi-state mechanism of the present invention; Figure 3 This is a diagram showing the parameter window and constraint relationship of the E-system of this invention; Figure 4 This is a flowchart illustrating the preparation process of the electrolyte for this invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Please see Figures 1-4 This invention provides a wide-temperature-range lithium battery electrolyte and its preparation method, comprising the following: The electrolyte contains the following components: A, B, C, D, and E: Component A: Low-temperature flow and low-resistance solvent matrix (ensuring acceptable ionic conductivity and low viscosity around −30°C). Component B: High-temperature / high-voltage stability and polymerization inhibition - trigger window controlled solvent (inhibits unwanted reactions during room temperature storage and cycling; allows interfacial reactions to occur in the presence of high temperature / high SOC / acid). Component C: Multi-lithium salt system (reduces LiPF6 dependence, reduces PF5 chain side reactions, and balances aluminum current collector stability and low-temperature conductivity); Component D: Basic interfacial film formation / low temperature fast charging lithium plating inhibitor (does not rely on the old FEC / VC approach, but is compatible with small-scale use); Component E: Acid-triggered crosslinking-self-healing interface enhancer system; Its characteristics are: E contains at least one latent polyol (E2) that can be triggered by HF / PF5 to release hydroxyl groups and one multifunctional epoxy unit (E1) that can undergo a ring-opening reaction, and optionally introduces a borate ester dynamic crosslinking modulation unit (E3), such that: When HF / PF5 is present: E2 → releases diol / polyol + consumes HF; subsequently, under the catalysis of PF5 / acidic environment, E1 undergoes a ring-opening reaction with the released alcohol to generate an organic-inorganic synergistic interface network film with a low glass transition temperature. When HF / PF5 is not significantly present (room temperature storage, low stress conditions): the E1 / E2 system remains dormant to avoid overall thickening / gelling of the electrolyte.

[0021] 3) Composition, range, and parameterization of each component 3.1 Component A: Low-temperature flow and low-resistance solvent matrix; Target metrics: Crystallization initiation temperature / pour point of the solvent system: preferably ≤−40°C (at least ≤−30°C); The dynamic viscosity of the system at −20°C is preferably ≤10 mPa·s (more preferably ≤6 mPa·s). The system contains at least one type of linear carbonate to balance the compatibility with graphite anodes and industrial maturity. Composition (A1–A3): A1 linear carbonates (30–70 wt%): It is selected from one or more of ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate. Specifically, it has low viscosity, low freezing point, some solubility for lithium salts, and provides basic ionic conductivity.

[0022] A2 low-pour-point carboxylic acid esters (5–25 wt%): It is selected from one or more of ethyl propionate, ethyl butyrate, and methyl propionate. It further reduces low-temperature viscosity and improves low-temperature wetting / saturation; however, components B, C, D, and E are needed to mitigate the risk of high-temperature side reactions.

[0023] A3 can be equipped with high dielectric constant fluxing units (0–15 wt%): γ-Butyrolactone or similar lactones can be used to improve lithium salt dissociation and low-temperature conductivity (if added, viscosity and high-temperature oxidation need to be controlled).

[0024] 3.2 Component B: Solvent for high-temperature / high-voltage stability and polymerization trigger window regulation; Target performance indicators: better oxidative stability in systems with a voltage of ≥4.4V (relative to linear carbonates), and the ability to complex / passivate Lewis acids such as PF5 to suppress unwanted cationic polymerization / solvent degradation at room temperature; Composition (B1–B2): B1 Nitrile solvents (5–35 wt%): 3-methoxypropionitrile is preferred, which improves low-temperature ionic conductivity, enhances lithium salt dissociation, and is relatively stable at high voltage.

[0025] B2 phosphate solvent (3–25 wt%): preferably triethyl phosphate or structurally similar alkyl phosphate, which improves high-temperature safety and high-voltage stability, and can also act as a Lewis base modulator to reduce the free activity of PF5, thereby inhibiting premature polymerization / thickening of the electrolytic liquid phase.

[0026] 3.3 Component C: Multi-lithium salt system (considering low-temperature conductivity, aluminum current collector and high-temperature side reaction chain) Target performance: Total lithium salt concentration: 0.9–1.3 mol / L; Reduce the sensitivity of the single LiPF6 system to the PF5 / HF chain side reaction; By introducing fluorosulfonamides / boron oxalates, a more inorganic enrichment interface is formed, which works synergistically with the E network membrane. Composition (C1–C3) C1 lithium hexafluorophosphate: 0.4–0.8 mol / L; C2 bis(fluorosulfonyl)imide lithium: 0.1–0.4 mol / L, with improved low-temperature ionic conductivity and enhanced tendency for interface inorganicization; C3 lithium difluorooxalate borate: 0.02–0.12 mol / L, promotes the formation of boron-fluorine-containing inorganic / organic composite layers at the interface, and reduces high-temperature side reactions and the tendency of transition metal migration.

[0027] 3.4 Component D: Basic interfacial film formation and low-temperature fast-charging lithium plating inhibitor additive Composition (D1–D2): D1 lithium difluorophosphate: 0.01–0.08 mol / L, provides a source of phosphorus-fluorine interface fragments, making SEI / CEI more inorganically enriched and reducing the sharp increase in interface resistance as temperature decreases.

[0028] D2 ethylene sulfite: 0.1–2.0 wt%, preferably 0.6–1.5 wt% (based on the final electrolyte), preferentially reduced to form a film at the negative electrode, forming a more stable and ion-conducting thin-layer structure to assist in low-temperature fast charging.

[0029] 4) Component E: Acid-triggered crosslinking-self-healing interface enhancer system 4.2 Composition and range of component E (E1–E3)

[0030] E1: Multifunctional epoxy unit (0.2–2.5 wt%);

[0031] E1 contains at least one compound (or a mixture thereof) with ≥2 epoxy groups, preferably a difunctional epoxy with a low glass transition temperature segment.

[0032] E1a Polyethylene glycol diglycidyl ether: Number average molecular weight: 250–500 g / mol (preferably 350–450 g / mol); Average functionality: ≥2 (based on epoxy groups); Amount added: 0.2–1.8 wt% (preferably 0.5–1.0 wt%); The epoxy equivalent falls within the range of 120–260 g / eq (which is beneficial for achieving interfacial network construction with low dosage; and takes into account solubility and avoids excessive stickiness).

[0033] E1b disiloxane-bridged difunctional epoxy (optional) For example, 1,3-bis(3-glycidyl ether propyl)tetramethyldisiloxane or similar compounds introduce Si–O–Si low glass transition temperature segments, which makes the subsequent interfacial network film remain flexible in the temperature range of −30~60°C, reducing the high-temperature chain risk of film embrittlement → regeneration side reaction → gas expansion.

[0034] Addition amount: 0–1.0 wt% (preferably 0.1–0.6 wt%); average functionality ≥2; and viscosity at 25°C not higher than the threshold that would significantly increase the overall viscosity of the electrolyte (the increase in electrolyte viscosity at 25°C after addition should be ≤30% as a process constraint).

[0035] E2: Acid-triggered latent polyols (0.05–1.2 wt%)

[0036] E2 must meet two conditions: the molecule contains ≥2 silyl ether bonds (Si–O–C), which can be triggered to break by HF / strong Lewis acid environment; after breaking, it releases a diol / polyol (as a ring-opening reaction crosslinking / chain growth unit of E1).

[0037] Preferred implementation: 1,4-Butanediol bis(tert-butyldimethylsilyl) ether; Number of silyl ether bonds: 2; Released polyol: 1,4-Butanediol (diol); Amount added: 0.05–0.8 wt% (preferably 0.15–0.40 wt%); At 25°C and without added acid, E2 does not undergo detectable significant deprotection in the electrolyte for 30 days (assuming a water content of <20 ppm); in the presence of HF (e.g., 50–500 ppm equivalent), E2 preferentially undergoes Si–O–C cleavage and consumes HF, releasing polyols.

[0038] E3: Borate ester dynamic crosslinking modulation unit (0.05–0.6 wt%)

[0039] Preferred implementation: Tributyl borate; Amount added: 0.05–0.5 wt% (preferably 0.10–0.25 wt%); It can form boron ester bonds with the diols released from E2; the boron center has Lewis acidity and can interact with fluorine-containing anions / oxygen-containing groups.

[0040] Let the total epoxy equivalent of E1 be Eeq (mol epoxy), and the hydroxyl equivalent released by E2 be Heq (mol–OH). Window: Eeq / Heq = 0.7–2.5 (preferably 0.9–1.8); Eeq / Heq is too small: the network is not well formed and it is difficult to form a continuous interface repair layer; Too high an Eeq / Heq ratio may lead to local overpolymerization, increased interfacial impedance, or the risk of inducing bulk thickening.

[0041] Simultaneously, a ratio window for E3 to Heq (e.g., Beq / Heq = 0.05–0.4 based on the number of boron centers) can be provided to regulate the dynamic crosslinking density.

[0042] Formula + Preparation Method Example 1: Electrolyte Formulation Solvent (based on a total solvent mass of 100 wt%) Ethyl methyl carbonate: 35 wt%; Diethyl carbonate: 20 wt% Ethyl propionate: 10wt% (CAS 105-37-3, molecular weight 102.13); 3-Methoxypropionitrile: 25wt% (CAS110-67-8, molecular weight 85.10); Triethyl phosphate: 10wt% (CAS 78-40-0, molecular weight 182.15); Lithium salts (based on final electrolyte concentration); Lithium hexafluorophosphate: 0.65 mol / L (CAS21324-40-3); Lithium bis(fluorosulfonyl)imide: 0.25 mol / L (CAS171611-11-3); Lithium difluorooxalate borate: 0.08 mol / L (CAS409071-16-5, molecular weight 143.77). Lithium difluorophosphate: 0.03 mol / L (CAS24389-25-1, molecular weight 107.91). Additive D (based on final electrolyte): Ethylene sulfite: 0.8wt% (CAS3741-38-6, molecular weight 108.12); Additive E (based on final electrolyte): E1a: Polyethylene glycol diglycidyl ether: 0.70 wt%; Polyethylene glycol diglycidyl ether, epoxy equivalent 250–320 g / eq (or weight equivalent WPE 250–320), determined according to GB / T 4612-2008.

[0043] E1b: 1,3-bis(3-glycidyl ether propyl)tetramethyldisiloxane: 0.30wt%; molecular weight 362.61g / mol, CAS126-80-7, this molecule contains 2 epoxy groups → epoxy equivalent approximately 181.3g / eq.

[0044] E2: 1,4-Butanediol bis(tert-butyldimethylsilyl) ether: 0.30 wt% CAS122795-01-1, molecular weight 318.6427 g / mol, acid-triggered deprotection releases 1 molecule of butanediol → 2 hydroxyl equivalents. Polyethylene glycol diglycidyl ether (controlled by epoxy equivalent): WPE example approx. 284 (may vary between batches / suppliers).

[0045] E3: Tributyl borate: 0.08wt% (molecular weight 230.15; flash point approximately 93℃).

[0046] Preparation method: Drying and moisture content control; All solvents, lithium salts, and additives must meet the following requirement before use: water content ≤ 20 mg / kg (20 ppm).

[0047] Moisture determination references: GB / T6283-2008 (General method of Karl Fischer method) or GB / T11133-2015 (Coulometric method).

[0048] Production environment: Dry room or glove box with dew point ≤−40℃ (oxygen / water ≤1ppm).

[0049] Prepare solvent stock solution (A+B): In an inert atmosphere (e.g., argon) glove box, weigh the solvents according to the above mass percentages: ethyl methyl carbonate, diethyl carbonate, ethyl propionate, 3-methoxypropionitrile, and triethyl phosphate.

[0050] Stir magnetically at room temperature (20–30°C) for 30–60 minutes to homogenize.

[0051] Stepwise salt dissolution (C) (to avoid local supersaturation and exothermic side reactions); Prepare the solvent stock solution under a dry, inert atmosphere and pre-cool it to 0–20°C; Lithium hexafluorophosphate was added in batches under stirring conditions, and the system temperature was kept below 20°C by external water bath or jacket cooling until the solution was clear and transparent. Subsequently, lithium difluorooxalate borate, lithium difluorophosphate, and lithium bis(fluorosulfonyl)imide are added sequentially and stirred until completely dissolved. If necessary, stirring is extended for 4–12 hours to ensure system homogeneity. If slight turbidity occurs, the electrolyte is allowed to stand to remove bubbles and then filtered through a 0.2-micron polytetrafluoroethylene filter membrane to obtain a clear electrolyte, which is then sealed and packaged.

[0052] Additives (D and E) are added: After the solvent mixing and lithium salt complete dissolution are completed and the system is clear and transparent, maintain the temperature at 20-30°C and continue stirring, and add the following in sequence: ethylene sulfite → multifunctional epoxy unit (add polyethylene glycol diglycidyl ether first, then add disiloxane diglycidyl ether, or premix the two and add them at once) → latent polyol → tributyl borate. After each substance is added, continue stirring for at least 20 minutes before adding the next substance, until the system returns to clarity and there are no visible microphases or suspensions, before proceeding to the next step of adding substances.

[0053] Continue stirring for 1–2 hours to ensure complete homogeneity of the system. If short-term turbidity occurs after the addition of the multifunctional epoxy unit, the system can be slowly heated to 30–35°C to promote dissolution. After dissolution, the temperature should be lowered to 20–30°C before continuing to add more materials, avoiding side reactions caused by prolonged high temperatures.

[0054] Filtration, Packaging and Storage: The electrolyte was filtered using a 0.2μm polytetrafluoroethylene membrane, and the appearance of the electrolyte before and after filtration was recorded (clear, transparent and without suspension).

[0055] Store in aluminum or fluorinated bottles, argon-filled and sealed, at 0–10°C away from light and heat sources; avoid contact with moisture and air during transportation and use.

[0056] As a supplement: Measurable parameters and determination methods for key raw materials: epoxy equivalent (GB / T4612-2008), moisture (GB / T6283-2008 or GB / T11133-2015), conductivity cell calibration (GB / T27502-2011), viscosity (GB / T265-1988).

[0057] Storage stability: Viscosity increase threshold at 25°C for 30 days, appearance change threshold (clarity / no colloid), and low-temperature salt precipitation test (−40°C for 24 hours).

[0058] Six electrolyte solutions (1 example + 5 comparative examples) All mass percentages below are based on a total solvent mass of 100 wt%; lithium salt concentrations are based on the final electrolyte concentration.

[0059] All electrolytes are assumed to have a water content of ≤20ppm (otherwise, high-temperature gas expansion would be amplified by water, and differences between groups would be masked by noise).

[0060] A. Embodiment of this application (Embodiment 1, E0) Solvent (A+B): Ethyl methyl carbonate: 35 wt%; Diethyl carbonate: 20 wt% Ethyl propionate: 10 wt% 3-Methoxypropionitrile: 25wt% Triethyl phosphate: 10 wt% Lithium salt (C): Lithium hexafluorophosphate: 0.65 mol / L; Lithium bis(fluorosulfonyl)imide: 0.25 mol / L; Lithium difluorooxalate borate: 0.08 mol / L; Lithium difluorophosphate: 0.03 mol / L; Basic film-forming additive (D): Ethylene sulfite: 0.60 wt%; Acid-triggered cross-linking self-healing system (E): Polyethylene glycol diglycidyl ether (number average molecular weight approximately 400 g / mol): 0.70 wt% 1,3-Bis(3-glycidyl ether propyl)tetramethyldisiloxane: 0.30 wt% 1,4-Butanediol bis(tert-butyldimethylsilyl) ether: 0.25 wt%; Tributyl borate: 0.15 wt% B.5 Pair Ratio:

[0061] Comparative Example 1 (C1: Commercial carbonate system benchmark)

[0062] Solvents: 25 wt% ethylene carbonate / 45 wt% ethyl methyl carbonate / 20 wt% diethyl carbonate / 10 wt% fluoroethylene carbonate; Lithium salt: Lithium hexafluorophosphate 1.0 mol / L; Additive: 1.0 wt% vinylene carbonate;

[0063] Comparative Example 2 (C2: Only A / B / C / D of this application are used, excluding E)

[0064] Solvent and lithium salt are exactly the same as in Example 1; No E added (no epoxy units, latent polyols, or borate esters added);

[0065] Comparative Example 3 (C3: tBS-GE single-molecule acid remover + air remover additive)

[0066] Solvent and lithium salt: Same as in Example 1; Additive: tert-butyldimethylsilyl glycidyl ether (tBS-GE) 0.80 wt%; E1 / E2 / E3 of Example 1 are not included; tBS-GE: The silyl ether group removes hydrofluoric acid and phosphorus pentafluoride, and the epoxy group reacts with carbon dioxide to form cyclic carbonates, thereby inhibiting bloating.

[0067] Comparative Example 4 (C4: only epoxy unit E1 added, without acid-triggered hydroxyl release gating and without dynamic borate ester)

[0068] Solvent and lithium salt: Same as in Example 1; join in: Polyethylene glycol diglycidyl ether 0.70 wt%; 0.30 wt% of 1,3-bis(3-glycidyl ether propyl)tetramethyldisiloxane; Not added: latent polyol (E2) and tributyl borate (E3);

[0069] Comparative Example 5 (C5: Add E1+E2, but do not add E3)

[0070] Solvent and lithium salt: Same as in Example 1; join in: Polyethylene glycol diglycidyl ether 0.70 wt%; 0.30 wt% of 1,3-bis(3-glycidyl ether propyl)tetramethyldisiloxane; 0.25 wt% 1,4-Butanediol bis(tert-butyldimethylsilyl) ether; Not added: Tributyl borate (E3).

[0071] III. Testing Standards and Test Items 1) National Standard (Cell Performance) GB / T31486-2024 "Electrical Performance Requirements and Test Methods for Power Batteries for Electric Vehicles"; GB / T31486-2015: Low-temperature discharge capacity: discharge test after being placed at −20℃±2℃ for 24h (6.3.8).

[0072] High-temperature discharge capacity: Discharge test after being placed at 55℃±2℃ for 5 hours (6.3.9).

[0073] High-temperature charge retention and capacity recovery: Charge retention and capacity recovery were measured after storage at 55℃±2℃ for 7 days (fully charged) (6.3.10.2).

[0074] Furthermore, its indicator thresholds (such as low-temperature capacity ≥70%, room temperature and high-temperature charge retention rate ≥85%, and capacity recovery ≥90%) can serve as magnitude constraints.

[0075] GB / T36276—2023 "Lithium-ion Batteries for Power Storage" can be cited in conjunction with this.

[0076] 2) National Standard (Basic Physicochemical Parameters) Calibration solution for conductivity meters: GB / T27502-2011 "Preparation method of calibration solution for conductivity measurement".

[0077] Viscosity: GB / T265-1988 "Determination of Kinematic Viscosity and Calculation of Dynamic Viscosity of Petroleum Products"; IV. Testing Methods 1) Low-temperature discharge capacity Referring to GB / T31486-20156.3.8: After the battery cell is fully charged, it is placed in an environment of −20℃±2℃ for 24 hours, and then discharged at the same temperature with a specified current to the cutoff voltage, and the discharge capacity is recorded.

[0078] Output metric: Capacity retention at −20°C (relative to initial capacity at 25°C).

[0079] 2) High-temperature discharge capacity Refer to 6.3.9: The cell is placed at 55℃±2℃ for 5 hours, and then discharged at the same temperature to measure the capacity.

[0080] 3) High-temperature charge retention and capacity recovery Referring to 6.3.10.2: After the battery cell is fully charged, it is stored at 55℃±2℃ for 7 days, left at room temperature for 5 hours, and then discharged to obtain the charge retention capacity; then it is charged and discharged according to the regulations to obtain the capacity recovery.

[0081] 4) Soft bag inflation During the 7-day fully charged storage period at 55°C (i.e., step b of 6.3.10.2), additional measurements were taken: Thickness of pouch cells (average of 3 points, micrometer accuracy 0.001mm). Thickness change rate = (thickness after storage - thickness before storage) / thickness before storage × 100%.

[0082] Optional: Puncture the collected gas volume (25℃, 1 atm) and normalize it to Ah (mL / Ah) as a more intuitive indicator of gas production.

[0083] 5) Low-temperature fast charging stress conditions Refer to the rate charging process of GB / T31486-20156.3.7, but change the temperature to −20℃ (this is a common industry standard process with temperature extension).

[0084] Operating conditions: -20℃: Discharge to cutoff voltage → let stand → charge at 2C constant current to 4.45V → constant voltage to 0.05C (or cut off after 30min) → let stand → discharge at 0.5C; cycle 50 times.

[0085] Output metrics: Capacity retention rate measured at 0.5C discharge at 25°C after 50 cycles (as a characterization of irreversible damage caused by low-temperature fast charging).

[0086] V. Test Data (n=3, mean ± standard deviation) Table 1: Physicochemical parameters of electrolyte

[0087] Table 2: Cell Performance

[0088] GB / T31486-2015 specifies that the low-temperature discharge capacity of lithium-ion battery modules should not be less than 70% of the initial capacity, and sets thresholds for charge retention rate at room temperature and high temperature not less than 85% and capacity recovery not less than 90%.

[0089] VI. Results Analysis Conclusion 1: Solvent / lithium salt engineering alone (Comparative Example 2) can improve low-temperature performance, but it is difficult to reduce high-temperature gas expansion to the same order of magnitude. Comparative Example 2 (without E) relative to Comparative Example 1: The capacity retention rate at −20℃ increased from 72% to 82% (significant improvement), indicating that A / B / C / D mainly solved the problems of low-temperature transport and the basic interface.

[0090] However, after 7 days of full-charge at 55℃, the gas expansion was still 9% (thickness change rate), and the gas production was 1.8 mL / Ah, indicating that the high-temperature chain side reaction had not been adaptively terminated.

[0091] Conclusion 2: tBS-GE (Comparative Example 3) can reduce gas expansion, but its improvement on low-temperature fast charging damage is limited, making it difficult to achieve optimal performance in both metrics simultaneously. Comparative Example 3 versus Comparative Example 2: Gas swelling decreased from 9.0% to 7.0%, and gas production increased from 1.8 to 1.2 mL / Ah (consistent with the literature description of tBS-GE acid removal + gas removal and swelling suppression).

[0092] However, after 50 cycles of fast charging at −20°C, the capacity retention rate was only 85%, which is still significantly lower than the 89% in the example.

[0093] Single-molecule acid / gas purification cannot automatically provide a low-temperature fast-charging friendly and high-temperature self-healing interface structure, even if it is effective for high-temperature gas expansion.

[0094] Conclusion 3: Adding only epoxy units (Comparative Example 4) resulted in side effects, indicating that simply adding them together does not guarantee good results. Comparative Example 4 (E1 only) did not significantly outperform Comparative Example 2 in terms of high-temperature gas expansion, and its low-temperature fast charging retention rate was actually worse (81%).

[0095] Adding epoxy compounds to the electrolyte does not necessarily bring positive effects; the lack of acid-triggered hydroxyl release gating (E2) and the lack of dynamic modulation (E3) can easily lead to unsuitable interfacial films (too hard / too thick / repeated cracking), resulting in higher polarization at low temperatures and a greater susceptibility to lithium plating-related damage.

[0096] Conclusion 4: After E2 (latent polyol) and E1 (multifunctional epoxy) form a reactive coupling, the performance indicators show a non-linear improvement; the addition of E3 further elevates them to the optimal range. Comparative Example 5 (E1+E2, no E3) has achieved the following: gas compression to 5.5%, gas production of 0.9 mL / Ah; and capacity retention increased to 87% after 50 cycles of low-temperature fast charging.

[0097] Example 1, based on Comparative Example 5, includes the addition of E3 (dynamic crosslinking modulation of borate esters): Gas expansion further decreased to 4.5%, with gas production at 0.70 mL / Ah; low-temperature fast charging retention further increased to 89%.

[0098] Existing technologies (such as tBS-GE) focus on removing hydrofluoric acid / phosphorus pentafluoride and carbon dioxide to suppress bloating.

[0099] However, given the inherent contradiction between low-temperature fast-charging lithium plating and high-temperature full-charge electrical expansion, simply removing acid / gas is insufficient to achieve both simultaneously. Low-temperature interface has low impedance and minimal damage during fast charging; high-temperature interface can adaptively repair itself and continuously suppress gas production.

[0100] By employing a reaction coupling system of latent polyols (which release hydroxyl groups upon acid triggering) + multifunctional epoxy (confined crosslinking) + borate esters for dynamic modulation, the interface can be constructed / repaired as needed when acidic byproducts appear at high temperatures, while avoiding bulk thickening side effects at low temperatures / room temperature. This achieves simultaneous optimization of both performance indicators (which cannot be achieved simultaneously in comparative examples 2, 3, 4, and 5). Those skilled in the art will recognize that the units and algorithm steps of the various examples described in conjunction with the embodiments disclosed herein can be implemented in electronic hardware, or a combination of computer software and electronic hardware. Whether these functions are implemented in hardware or software depends on the specific application and design constraints of the technical solution. Those skilled in the art can use different methods to implement the described functions for each specific application, but such implementation should not be considered beyond the scope of this application.

[0101] Those skilled in the art will understand that, for the sake of convenience and brevity, the specific working processes of the systems, devices, and units described above can be referred to the corresponding processes in the foregoing method embodiments, and will not be repeated here.

[0102] In the several embodiments provided in this application, it should be understood that the disclosed systems, apparatuses, and methods can be implemented in other ways. For example, the apparatus embodiments described above are merely illustrative; for instance, the division of units is only a logical functional division, and in actual implementation, there may be other division methods. For example, multiple units or components may be combined or integrated into another system, or some features may be ignored or not executed. Furthermore, the coupling or direct coupling or communication connection shown or discussed may be through some interfaces; the indirect coupling or communication connection between apparatuses or units may be electrical, mechanical, or other forms.

[0103] The units described as separate components may or may not be physically separate. The components shown as units may or may not be physical units; that is, they may be located in one place or distributed across multiple network units. Some or all of the units can be selected to achieve the purpose of this embodiment according to actual needs.

[0104] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A wide-temperature-range lithium battery electrolyte, characterized in that: The product comprises a solvent system, a lithium salt, ethylene sulfite, and component E. The solvent system includes linear carbonates, low-pour-point carboxylic esters, nitrile solvents, and phosphate solvents. The lithium salt is lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalate borate, and lithium difluorophosphate, with a total lithium salt concentration of 0.9 to 1.3 mol / L. Component E comprises 0.2 to 2.5% by mass of a multifunctional epoxy unit, 0.05 to 1.2% by mass of 1,4-butanediol bis(tert-butyldimethylsilyl) ether, and 0.05 to 0.6% by mass of tributyl borate. The multifunctional epoxy unit contains polyethylene glycol diglycidyl ether and 1,3-bis(3-glycidyl etherpropyl)tetramethyldisiloxane, and the ratio of the epoxy equivalent of the multifunctional epoxy unit to the hydroxyl equivalent released by 1,4-butanediol bis(tert-butyldimethylsilyl) ether is 0.7 to 2.

5.

2. The wide-temperature-range lithium battery electrolyte according to claim 1, characterized in that: Based on the total mass of solvents, linear carbonates consist of 35% by mass of ethyl methyl carbonate and 20% by mass of diethyl carbonate, low-pour-point carboxylic acid esters consist of 10% by mass of ethyl propionate, nitrile solvents consist of 25% by mass of 3-methoxypropionitrile, and phosphate ester solvents consist of 10% by mass of triethyl phosphate.

3. The wide-temperature-range lithium battery electrolyte according to claim 1, characterized in that: The concentrations are: lithium hexafluorophosphate (0.65 mol / L), lithium bis(fluorosulfonyl)imide (0.25 mol / L), lithium difluorooxalate borate (0.08 mol / L), and lithium difluorophosphate (0.03 mol / L).

4. The wide-temperature-range lithium battery electrolyte according to claim 1, characterized in that: The ethylene sulfite content is 0.6 to 1.5% by mass.

5. The wide-temperature-range lithium battery electrolyte according to claim 1, characterized in that: The amount of polyethylene glycol diglycidyl ether added is 0.5 to 1.0% by mass, and its epoxy equivalent is 250 to 320 g per dose.

6. The wide-temperature-range lithium battery electrolyte according to claim 1, characterized in that: The amount of 1,3-bis(3-glycidyl ether propyl)tetramethyldisiloxane added is 0.1 to 0.6% by mass, and its molecule contains two epoxy groups.

7. The wide-temperature-range lithium battery electrolyte according to claim 1, characterized in that: The amount of 1,4-butanediol bis(tert-butyldimethylsilyl) ether added is 0.15 to 0.40% by mass, and its molecule contains at least two silyl ether bonds.

8. The wide-temperature-range lithium battery electrolyte according to claim 1, characterized in that: The amount of tributyl borate is 0.10 to 0.25% by mass, and the ratio of the number of boron centers in the tributyl borate to the hydroxyl equivalent released by 1,4-butanediol bis(tert-butyldimethylsilyl) ether is 0.05 to 0.

4.

9. A method for preparing a wide-temperature-range lithium battery electrolyte, characterized in that: Includes the following steps: Under an inert atmosphere, ensure that the water content of the solvent, lithium salt, and additives does not exceed 20 mg / kg; mix the solvent system and stir. The solvent system was first mixed under an inert atmosphere and cooled to 0–20°C. Lithium hexafluorophosphate was added in batches with stirring. Lithium difluorooxalate borate and lithium difluorophosphate were added first at 20–30°C, followed by lithium bis(fluorosulfonyl)imide, and finally stirred until clear. Ethylene sulfite, multifunctional epoxy unit and 1,4-butanediol bis(tert-butyldimethylsilyl) ether were added in sequence. Tributyl borate was then pre-diluted with the solvent system and added dropwise. The mixture was filtered and sealed for storage.

10. The preparation method according to claim 9, characterized in that: After adding each substance, continue stirring for at least 20 minutes; filter using a 0.2-micron PTFE filter membrane; after filtration, pack into an aluminum or fluorinated bottle, seal with argon, and store at 0 to 10 degrees Celsius away from light.

Citation Information

Patent Citations

  • Low-temperature lithium battery electrolyte and lithium battery

    CN115602927A

  • Electrolyte composition comprising organosilicon compounds

    US20250055030A1